Isolasi dan Karakterisasi Asam Oleat dari Kulit Buah Kelapa Sawit (Elais guinensis Jacq.) - Mora, Enda; Selpas, Nandhana (Jurnal Penelitian Farmasi Indonesia, 2013)
A compound has been isolated from n-hexane extract of fruits skin of palm (Elais guinensis Jacq). Separation of 2 g extract was conductedby using column chromatography with step gradient polarity method and using n-heksana, ethyl acetate and methanol as the eluents. Thisisolated compound is yellow fatty (573.9 mg, 28.96%) which melted at 26-28oC. Based on NMR spectroscopic datas, including, 1H-NMR, 1H-1H COSY, 13C-NMR and DEPT, the compound was suggested as oleic acid.